A aplicação dos direitos humanos nas decisões da Organização Mundial do Comércio (OMC) - Niess, Luciana Toledo Távora (2012)
The World Trade Organization (WTO) is an international organization which has a system of rules that organizes the world market by defining lawful and unlawful behavior, and providing mechanisms to ensure compliance with its rules. Nevertheless, some multilateral trade negotiations may violate Human Rights. This study aims the application of these rights into WTO decisions, since they are essential for human dignity and consequently for the development of a State. The research of national and foreign legislation, doctrine and jurisprudence, made in Brazil and in the International World Trade Organization, in Geneva, Switzerland, guided the study elaboration. The analysis purpose has been reached by reason of the review successfully verifies the way that WTO has been deciding the subjects related to international trade which oppose human rights or make harm to the environment. Additionally, it evaluates decisions in which the economic value overwhelms fundamental human rights. Finally, it presents reasoning and proposals to the application of inherent human rights to the WTO negotiations